A Narrative Review of Stresses and Conflicts of Marketing in Social Organizations - Saini, Kartikay; Khan, Nusrat; Khan, Mohd. Azmi (Prabandhan: Indian Journal of Management, 2024)
Purpose : This paper focused on a narrative review (NR) of the stresses and conflicts of marketing in social organizations in the disability sector. These stresses and conflicts refer to the challenges, constraints, and other conflicting objectives within a social organization. Methodology : The paper was based on a review of research papers that were gathered from different databases, like EBSCO Host and Google Scholar, and publisher groups like Sage, Springer, Taylor & Francis, Elsevier, and Emerald Publishing. The study adopted inclusion and exclusion criteria for including the papers, and finally, 68 research articles were reviewed thoroughly to understand and highlight the stresses and conflicts of marketing in voluntary and non-profit organizations. Findings : This study found that social organizations face several constraints coming from different areas. Especially with respect to the marketing of social organizations for the differently abled, there are several challenges faced at different levels, like the organizational level, the marketing practitioner’s level, and the donor front. Practical Implications : This paper intended to create awareness amongst the marketing professionals of social organizations of the various constraints that exist in the marketing of these organizations. This will help organizations strategize their marketing initiatives in a more focused manner and tackle the stresses and conflicts mentioned with ease. Originality : This paper portrayed its uniqueness by highlighting the stresses and conflicts of marketing for disability organizations that remain unaddressed in past studies, despite these being the key issues to be overcome for sustainability and existence.